Military prose in Russian literature (On a material of a story by V. Bykov «Sotnikov») - el-Gebaly, Mohamed Nasr; Abdo, Dina Mohamed (Journal of Oriental Studies, 2016)
This paper analyzes the features of the genre military prose in Russian literature, historical overview of the genre, defining the location of this topic in V. Bykov’s prose. The material of the research is a writer’s novel «Sotnikov».Moral choices and moral dilemmas are the leitmotif of Bykov’s novel. The work has proved the importance of this topic in the writer’s literary creativity.